A recurrent cross-sectional qualitative study exploring how low-income mothers define snacks and reasons for offering snacks during infancy. (1st July 2021) - Moore, Amy M.; Vadiveloo, Maya; McCurdy, Karen; Bouchard, Kelly; Tovar, Alison
Abstract: Despite rapid increases in snacking in recent decades, little is known about snacking during infancy. This study explored how low-income mothers define snacks and their reasons for offering snacks during infancy. A recurrent cross-sectional qualitative approach was used to identify themes from semi-structured interviews with low-income mothers when their infants were 6 and 12 months of age. A purposive sample of mothers (N = 15) was recruited from Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) offices and childcare centers serving low-income families in Rhode Island. Mothers also completed demographic and infant feeding questionnaires. Independent thematic analyses were conducted to identify themes from the 6 and 12 month interviews. Themes from the 6 month interviews for how mothers defined snacks were: snacks are consumed between meals, snacks are smaller portions, and snacks are sweet . Themes from the 12 month interviews also included snacks are consumed between meals and snacks are smaller portions with one additional theme: snacks do not include all food groups . Themes from the 6 month interviews for the reasons mothers offered snacks were: infants seemed hungry, infants showed interest, and snacks help manage behavior . Themes from 12 month interviews also included snacks help manage behavior with two additional themes: snacks expose infants to different flavors and snacks expose infants to different textures . Findings suggest that snacks are commonly offered during infancy and that mothers define snacks as smaller portions that help with hunger between meals. However, during early infancy mothers describe snacks as sweet, and across infancy report using snacks to manage behavior, underscoring the importance of providing parents with guidance on healthy snacking during the first year of life.